2017
DOI: 10.1128/jb.00790-16
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Understanding the Molecular Basis Underlying Functional Diversification of Cyclic Dinucleotide Turnover Proteins

Abstract: Cyclic di-GMP was the first cyclic dinucleotide second messenger described, presaging the discovery of additional cyclic dinucleotide messengers in bacteria and eukaryotes. The GGDEF diguanylate cyclase (DGC) and EAL and HD-GYP phosphodiesterase (PDE) domains conduct the turnover of cyclic di-GMP. These three unrelated domains belong to superfamilies that exhibit significant variations in function, and they include both enzymatically active and inactive members, with a subset involved in synthesis and degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 100 publications
2
41
0
Order By: Relevance
“…In addition, we identified three novel EAL domain proteins PdeU1, PdeU2, and PdeU3 in UPEC strains (Table ); PdeU1 was present in B‐11870 and 80//6, PdeU2 was found in B‐11870, and PdeU3 in B‐8638. Extended conserved aa signatures are critical for PDE activity (Liang, ; Römling, Liang, & Dow, ; Römling et al., ). Conservation of the signature motifs of catalytic residues indicated that only PdeU1 is potentially active (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we identified three novel EAL domain proteins PdeU1, PdeU2, and PdeU3 in UPEC strains (Table ); PdeU1 was present in B‐11870 and 80//6, PdeU2 was found in B‐11870, and PdeU3 in B‐8638. Extended conserved aa signatures are critical for PDE activity (Liang, ; Römling, Liang, & Dow, ; Römling et al., ). Conservation of the signature motifs of catalytic residues indicated that only PdeU1 is potentially active (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, strains showed variability in the number of c-di-GMP turnover proteins ( (Liang, 2015;Römling, Liang, & Dow, 2017;Römling et al, 2013). Conservation of the signature motifs of catalytic residues indicated that only PdeU1 is potentially active ( Figure S4).…”
Section: Presence and Sequence Of C-di-gmp Metabolizing Proteins DImentioning
confidence: 99%
“…Therefore, our data indicate that edcA is not a PDE in E. amylovora. PDEs respond to a wide range of specific stimuli and can be functional in localized areas within the cell (36,37). The experimental conditions under which we evaluated c-di-GMP levels might restrict the expression and/or enzymatic activity of PdeA and PdeB, thus not resulting in a measurable impact on c-di-GMP levels in the cell under these conditions, whereas these enzymes might have more significant contributions in other environments.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse signaling pathways are comprised of specific enzyme classes that produce and degrade a signal, as well as biomolecules that respond to the signal. In cyclic dinucleotide signaling, synthases produce the cyclic dinucleotide (CDN) signal from nucleotide triphosphate (NTP) substrates, phosphodiesterases (PDEs) degrade the CDN via hydrolysis of one or both phosphodiester linkages, and effectors, including transcription factors, enzymes, and riboswitches, respond to the CDN signal (Römling et al , ; ). So far, three CDN second messengers have been found to control critical bacterial processes, including biofilm formation, cell wall homeostasis, intestinal colonization and transient surface interactions (Davies et al , ; Corrigan and Gründling, ; Römling et al , ; Hallberg et al , ).…”
Section: Introductionmentioning
confidence: 99%